2022
DOI: 10.1038/s41420-022-01010-8
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 and FTO are involved in miR-5581-3p-mediated inhibition of cell migration and proliferation in bladder cancer

Abstract: Previous research evidence suggests that microRNAs (miRNAs) play an indispensable role in onset and progression of bladder cancer (BCa). Here, we explored the functions and mechanisms of miR-5581-3p in BCa. miR-5581-3p, as a tumor suppressor in BCa, was detected at a lower expression level in BCa tissue and cells in contrast with the non-malignant bladder tissue and cells. Over-expression of miR-5581-3p remarkably dampened the migration and proliferation of BCa in vitro and in vivo. SMAD3 and FTO were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…3D ) [ 72 ]. Sun et al [ 73 ] reported that miR-5581-3p can inhibit the migration of BCa cells by targeting FTO (Fig. 3E ).…”
Section: The Interaction Between M6a Modification and Ncrnas In Urina...mentioning
confidence: 99%
“…3D ) [ 72 ]. Sun et al [ 73 ] reported that miR-5581-3p can inhibit the migration of BCa cells by targeting FTO (Fig. 3E ).…”
Section: The Interaction Between M6a Modification and Ncrnas In Urina...mentioning
confidence: 99%
“…RNA methylation-related proteins have become promising targets for cancer therapy (24). Pan-cancer data were retrieved from the UCSC database, and from this dataset, we extracted the expression pro les of the SMAD3 gene along with 44 marker genes related to Class III RNA modi cation (comprising m1A (10), m5C (13), and m6A (21) genes) within each sample. Subsequently, Pearson correlation coe cients were computed to elucidate the associations between SMAD3 and these marker genes within the context of ve distinct immune pathways.…”
Section: Dna Methylation and Rna Modi Cation Analysismentioning
confidence: 99%
“…Subsequent studies unveiled that NK-3-S1KD, a genetically engineered stable Smad3-silenced human NK cell line, effectively curbs cancer progression in xenografted mouse models with human liver cancer and melanoma (9). Elevated SMAD3 expression levels also correlate with the progression and prognosis of various cancers, including bladder urothelial carcinoma (BLCA), colon adenocarcinoma (COAD), prostate adenocarcinoma (PRAD), and cervical carcinoma (CESC) (10)(11)(12)(13)(14). Additionally, numerous drugs have been found to regulate tumor proliferation and metastasis through SMAD3, including CDK4 inhibitors and doxorubicin, which induce breast cancer cell apoptosis via SMAD3.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, miRNAs can also affect the FTO process during m 6 A modifications. Sun et al ( Sun et al, 2022 ) reported that miR-5581–3p is a tumour suppressor in BC, and FTO is regarded as a direct downstream target of miR-5581–3p. miR-5581–3p suppressed FTO synthesis and inhibited BC progression and proliferation via the miR-5581–3p/FTO/Matrix metallopeptidase 9 (MMP9) axis.…”
Section: Role Of M 6 a Regulators In The Progressi...mentioning
confidence: 99%